Rhodiola rosea L. and Alzheimer's Disease: From Farm to Pharmacy. (11th January 2016) - Nabavi, Seyed Fazel; Braidy, Nady; Orhan, Ilkay Erdogan; Badiee, Arash; Daglia, Maria; Nabavi, Seyed Mohammad
Abstract : Rhodiola rosea L. (roseroot) is a common member of the family Crassulaceae, known as one of the most important popular medicinal plants in the northern region of Europe. The roots of R. rosea possess a wide range of pharmacological activities such as antioxidant, antiinflammatory, anticancer, cardioprotective, and neuroprotective effects that are because of the presence of different phytochemicals such as phenols and flavonoids. In addition, the presence of salidroside, rosavins, and p ‐tyrosol are responsible for its beneficial effects for the treatment of on depression, fatigue, and cognitive dysfunction. A plethora of studies report that R. rosea has potent neuroprotective effects through the suppression of oxidative stress, neuroinflammation, and excitotoxicity in brain tissues and antagonism of oncogenic p21‐activated kinase. However, to our knowledge, no review articles have been published addressing the neuroprotective effects of R. rosea . Therefore, the present article aims at critically reviewing the available literature on the beneficial effects of R. rosea on as a therapeutic strategy for the treatment of Alzheimer's disease and other neurodegenerative diseases where oxidative stress plays a major role in disease development and progression. We also discuss the cultivation, phytochemistry, clinical impacts, and adverse effects of R. rosea to provide a broader insight on the therapeutic potential for this plant. Copyright © 2016 John Wiley & Sons, Ltd.